Measurement of long-range pseudorapidity correlations and azimuthal harmonics in √sNN=5.02 TeV proton-lead collisions with the ATLAS detector - Onofre, A. (2014)
Measurements of two-particle correlation functions and the first five azimuthal harmonics, v1 to v5, are presented, using 28 nb−1 of p + Pb collisions at a nucleon-nucleon center-of-mass energy of √sNN = 5.02 TeV measured with the ATLAS detector at the LHC. Significant long-range “ridgelike” correlations are observed for pairs with small relative azimuthal angle (|φ| < π/3) and back-to-back pairs (|φ| > 2π/3) over the transverse momentum range 0.4 < pT < 12 GeV and in different intervals of event activity. The event activity is defined by either the number of reconstructed tracks or the total transverse energy on the Pb-fragmentation side. The azimuthal structure of such long-range correlations is Fourier decomposed to obtain the harmonics vn as a function of pT and event activity. The extracted vn values for n = 2 to 5 decrease with n. The v2 and v3 values are found to be positive in the measured pT range. The v1 is also measured as a function of pT and is observed to change sign around pT ≈ 1.5–2.0 GeV and then increase to about 0.1 for pT > 4 GeV. The v2(pT), v3(pT), and v4(pT) are compared to the vn coefficients in Pb + Pb collisions at √sNN = 2.76 TeV with similar event multiplicities. Reasonable agreement is observed after accounting for the difference in the average pT of particles produced in the two collision systems.